Detecting actionable mutations from matched plasma-based versus tissue next-generation sequencing in advanced non-small cell lung cancer: a retrospective single centre analysis on site - Christophe Bontoux; Caroline Lacoux; Jonathan Benzaquen; Jacques Boutros; Guylène Rignol; Elodie Long-Mira; Sandra Lassalle; Maryline Allegra; Doriane Bohly; Mathieu Garcia; Christelle Bonnetaud; Olivier Bordone; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Liquid biopsies (LB) are used increasingly to detect actionable mutations in patients newly diagnosed with advanced non-small cell lung cancer (aNSCLC), though tissue biopsies (TB) still remain the gold standard. The value of systematically combining LB and TB next-generation sequencing (NGS) for genomic profiling in these patients remains controversial. Methods This single-centre retrospective study included 102 matched TB and LB samples collected from aNSCLC patients at diagnosis. Four circulating free DNA (cfDNA)-based NGS assays (1–4) were compared on site for performance and concordance with TB to detect ESMO Scale for Clinical Actionability of molecular Targets (ESCAT) I/II. Additionally, cfDNA droplet digital PCR methylation (ddPCR-met) testing estimated the tumour fraction to refine the interpretation of wild-type (WT) results. Results Out of 102 patients, 13% had stage IIIB disease, and 11% presented with brain-only metastases. Adenocarcinoma was the predominant subtype (84%). Ninety LB samples yielded interpretable results across the four assays. Positive percent agreement with TB ranged from 56% (assay 2) to 79% (assay 4), with high concordance, particularly for single-nucleotide variants (SNVs). Hybrid capture-based assays (3 and 4) detected eight and seven gene fusions, respectively, while amplicon-based assays (1 and 2) detected only two each. Assay 3 only identified 12 MET amplifications, five of which were confirmed by fluorescence in situ hybridisation (FISH) but were missed by TB-based NGS. Five out of six negative cfDNA samples with ddPCR-met testing were WT across all assays. The plasma-first approach added incremental value, up to 21% (assay 3). Amplicon-based assays were faster and required less input of DNA for analysis. Patients with stage IIIB or brain-only metastases were significantly more likely to have negative/low levels of cfDNA ddPCR-met. Conclusions LB-based NGS demonstrated high concordance with TB in newly diagnosed aNSCLC, particularly for detection of SNV. Hybrid capture assays showed superior performance in identifying gene fusions and MET amplifications. The incremental value of a plasma-first strategy was limited in this real-life study. Thus, LB-based NGS on site should be seen as a complementary tool to TB-based NGS or an alternative when tissue samples are unavailable. Additionally, cfDNA methylation analysis enhances diagnostic accuracy in specific cases.